Change in Angina Symptom Status After Acute Myocardial Infarction and Its Association With Readmission Risk: An Analysis of the Translational Research Investigating Underlying Disparities in Acute Myocardial Infarction Patients' Health Status (TRIUMPH) Registry. Issue 6 (June 2016) - Doll, Jacob A.; Tang, Fengming; Cresci, Sharon; Ho, P. Michael; Maddox, Thomas M.; Spertus, John A.; Wang, Tracy Y.
Abstract : Background: Angina is common both before and after myocardial infarction (MI). Whether the change in angina status within the first 30 days after MI is associated with subsequent readmission and angina persistence is unknown. Methods and Results: We studied 2915 MI patients enrolled at 24 hospitals in the Translational Research Investigating Underlying Disparities in Acute Myocardial Infarction Patients' Health Status (TRIUMPH) registry. Angina before and 30 days after MI was assessed with the Seattle Angina Questionnaire. Patients were divided into angina‐free pre‐ and post‐MI (−/−), resolved angina (+/−), new angina (−/+), and persistent angina (+/+) groups. Multivariable proportional hazards and hierarchical modified Poisson models were performed to assess the association of each group with all‐cause readmission, readmission for MI or unplanned revascularization, and angina persistence at 1 year. Overall, 1293 patients (44%) had angina before their MI and 849 (29%) reported angina within 30 days of discharge. Patients with post‐MI angina were more likely to be younger, nonwhite, and uninsured. Compared with patients who were angina‐free pre‐ and post‐MI, 1‐year all‐cause readmission risks were significantly higher for patients with persistent angina (hazard ratio [HR], 1.35; 95% CI 1.06–1.71) or new angina (HR, 1.40; 95% CI, 1.08–1.82). At 1 year, angina was present in 22% of patients and was more likely if angina was persistent (HR, 3.55; 95% CI, 3.05–4.13) or new (HR, 3.38; 95% CI, 2.59–4.42) at 30 days compared with patients who were angina‐free pre‐ and post‐MI. Conclusions: Post‐MI angina, whether new or persistent, is associated with higher likelihood of readmission. Prioritizing post‐MI angina management is a potential means of improving 1‐year outcomes.